(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1994)
This paper deals with the description of a rich ammonoid assemblage collected in calcareous lenses outcropping within the Ladinian Calcare di Esino of Val Parina (Northern ltaly). The faunas come from lenses outcropping on the northern slope opposite of Val di Lavaggio. The Material was collected by M. Gervasutti and is stored in the Museo Civico di Scienze Naturali "E. Caffi" in Bergamo (Italy). More than 60 species were identified, including about twenty new species and three new genera: Parinaia (fam. Ceratitidae), Rossiceras (fam. Hungaritidae) and Gervasuttia (fam. Aplococeratidae). The new taxa give a substantial contribution to the knowledge of the poorly studied Tethyan faunas ofthe Ladinian. Whether these faunas are endemic or not is at present difficult to determine. The fossiliferous levels extend from 550 m to 850 m altitude. In this interval 5 assemblages were recognized (from bottom to top): 1) Assemblage with Chieseiceras perticaense, Norites, Gevanites, Iberites, Epigymnites, Aplococeras, Proarcestes, Procladiscites, Eoprotrachyceras, Monophyllites; 2) Assemblage with Eoprotrachyceras recubariense, Norites, Chieseiceras, Gevanites, Sturia, Epigymnites, Aplococeras, Eoprotrachyceras, Monophyllites; 3)Assemblage with Protrachyceras margaritosum, Iberites, Epigymnites, Gervasuttia Argolites, Monophyllites; 4) Assemblage with Gervasuttia, Arpadites, Protrachyceras, Monophyllites; 5) Assemblage with Protrachyceras longobardicum, Sageceras, Iberites, Rossiceras, Sturia, Epigymnites, Praepinacoceras, Proarcestes, Protrachyceras, Detoniceras, Arpadites, Argolìtes, Monophyllites. The assemblages 1) and 2) can be ascribed to the Curionii Zone; assemblages 3) and 4) to the Gredleri Zone, and assemblage 5) to the lower part of the Archelaus Zone.